2023
DOI: 10.3390/agronomy13112768
|View full text |Cite
|
Sign up to set email alerts
|

Tithonia diversifolia Improves In Vitro Rumen Microbial Synthesis of Sheep Diets without Changes in Total Gas and Methane Production

Simón Pérez-Márquez,
Vagner S. Ovani,
Paulo de Mello Tavares Lima
et al.

Abstract: Among the alternatives identified as capable of making livestock farming a more efficient activity and reducing its environmental impact, the use of feeds with high digestibility and the use of non-conventional fodder species can be highlighted. Tithonia diversifolia (Hemsl.) A. Gray (TD) has already gained attention as a feed for ruminants. Nonetheless, there has been little discussion about the impacts of this plant on the rumen dynamics that lead to better animal performance. The aim of this study was to as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…It has been reported that DMD provide a poor indication of true fermentability (McSweeney et al 1999 ). Instead, the authors recommended measuring end products of in vitro fermentation such as ammonia, short and branched chain fatty acids to better assess the nutritional value of forage plants (Pérez-Márquez et al 2023 ). In this regard, the present study shows a suitable concentration of TVFA in different melons’ mesocarps.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DMD provide a poor indication of true fermentability (McSweeney et al 1999 ). Instead, the authors recommended measuring end products of in vitro fermentation such as ammonia, short and branched chain fatty acids to better assess the nutritional value of forage plants (Pérez-Márquez et al 2023 ). In this regard, the present study shows a suitable concentration of TVFA in different melons’ mesocarps.…”
Section: Discussionmentioning
confidence: 99%